Evaluation Of The Implementation Of The Internal Audit Capability Model (IACM) Level 3 In The Supervision System Of The Inspectorate General Of The Ministry Of Agriculture - Parulian Simanjuntak, Gordon; Sensi W, Ludovicus (Publisher Cv. Inara, 2023)
This thesis discusses the IACM level 3 evaluation of the supervision system of the Inspectorate General of the Ministry of Agriculture to determine the gap between the capability conditions of the Inspectorate of the Ministry of Agriculture and the needs of stakeholders, and areas of improvement that need to be followed up to provide suggestions for improving the capability of the Inspectorate General of the Ministry of Agriculture. The research method used is a qualitative method with a case study approach. The informants in this research consisted ofSecretary of the Inspectorate General, Inspectorate I, Inspectorate III, Inspectorate IV,Investigation Inspectorate andInspector IIInspectorate General of the Ministry of Agriculture.The data used in this research consists of primary data and secondary data. Data collection was carried out through document analysis and interviews. Qualitative data analysis is carried out involving data reduction, data presentation, and drawing conclusions. The results of this research show that the supervision activities carried out by the Inspectorate General of the Indonesian Ministry of Agriculture are at Level 3 or only carry out supervision activities on compliance audits.In general, the Office of the Inspector General of the Ministry of Agriculture has reached level 3 (integrated). Within each element, all relevant internal audit policies, processes and procedures are defined, documented and integrated.